Analisis Pemanfaatan TrueNAS Pada Kanreg VII BKN Palembang - Herdiansyah, M. Izman; Novendra, Hasrudi (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
Network Attached Storage (NAS) is a particular file storage device that makes data available continuously. Each computer network has server machines and client machines that are connected, and a specific NAS server device handles file sharing and data storage requests by providing fast service—storage service is safe and efficient. Network Attached Storage (NAS) is a reliable and scalable storage media solution with relatively low costs compared to renting a paid data storage server such as Google Drive. In designing this NAS, we use the open-source NextCloud software to back up or store data in the Cloud. This software has features similar to similar services such as Dropbox or Google Drive. This software is also intended for clients who want to access the storage provided and can be supported by various operating systems such as Windows, Linux, IOS, and Android. This NAS design was built to meet the data storage needs of employees in the INKA Kanreg VII BKN Palembang sector, whose needs are always increasing, including the ability to share files or data easily